Mobile Payment Transaction Model with Robust Security in the NFC-HCE Ecosystem with Secure Elements on Smartphones - Harnaningrum, Lucia Nugraheni (International Journal of Advanced Computer Science and Applications, 2022)
The Near Field Communication embedded (NFC-embedded) smartphone consists of two ecosystems, namely Near Field Communication Subscriber Identity Module Secure Element (NFC-SIM-SE) and Near Field Communication Host Card Emulation (NFC-HCE). NFC-SIM-SE places secure elements in smartphones, while NFC-HCE places secure elements in the cloud. In terms of security, the location of secure elements in the cloud is one of the weaknesses of NFC-HCE. The APL-SE transaction model is developed as a solution to improve transaction security with NFC-enabled mobile. This model moves the secure elements of the NFC-HCE ecosystem from the cloud to the smartphone so that when the transaction is made, the smartphone does not communicate with the outside network to access the secure element. The APL-SE transaction model is tested using dummy data to calculate the processing time measurements for each step. The model is also tested for the encryption process. The encrypted data is compared with the original data, then the randomness is calculated. This transaction model is also tested by looking at the data randomness, which shows that the encrypted data is declared random. Random data increases data security. The transaction model test shows that the transaction runs well because the encrypted data is proven random, and the execution time is 1,074 ms. The time of 1,074 ms is far below an attacker's time to decipher the encrypted data. Random and fast encryption results indicate that transactions are secure. This achievement makes the opportunity for attackers to manipulate data small, so security is increased